THE IMPACT OF IELTS ON ENGLISH LANGUAGE LECTURERS’ TEACHING PRACTICE AND PROFESSIONAL DEVELOPMENT AT DONG NAI TECHNOLOGY UNIVERSITY - Nguyen Thi Thanh Van*; Nguyen Thi Hong Lien (Tạp chí Khoa học)
This study examines the impact of IELTS tests on the teaching practices and professional development of 20 lecturers from the Faculty of Foreign Languages at Dong Nai University of Technology. Through online surveys and in- depth interviews, the research sheds light on IELTS as an assessment tool for evaluating graduates' language proficiency and as a factor influencing teaching methodologies and lecturers' professional growth. The findings reveal that IELTS positively impacts various aspects, including teaching content, pedagogical methods, and the enhancement of lecturers' English proficiency and teaching competencies. However, participants also faced challenges, particularly in teaching speaking and writing skills, and expressed the need for a comprehensive training course on IELTS assessment. The study underscores the importance of equipping educators with a thorough understanding of language assessment, as it is a powerful tool for improving the quality of teaching and learning in modern education.